Avaliação da microinfiltração bacteriológica na interface pilar/implante em Implantes Hexágono Externo com diferentes torques - Silva Neto, João Paulo da (2009)
The aim of this study was to evaluate the microleakage of abutment/implant interface (A/I) in external hexagon implants (HE) with different torques values. Nine HE implants extern torque with conical abutments and screws were randomly selected and divided into three groups: V0.5, V1.0 and V1.5 and used in two experimental steps. A Escherichia coli bacterial suspension (BS) was prepared to the density of 0,5 McFarland standard and inoculated in the inner parts of the implants. The clarity of the broth was observed each 24 hours during 14 days, and after this period, the bacterial viability was checked by a microbiological test. In the first step, implants were inoculated as follows: V0.5- with 0.5 μL of BS; V1.0- with 1.0 μL of BS; and V1.5- with 1.5 μL of BS. Then the abutments were wrench following the manufacturer s recommended torque values. In the second step, the experiment design was repeated three times for checking the reproducibility and the assemblies were divided into three groups with different torques values: T10- abutments wrench with 10 Ncm; T20- wrench with 20 Ncm and T32- wrench with 32 Ncm. The results showed that in the first step all the samples of V1.0 and V1.5 groups presented cloudy broth on the control tubes in the first 24 hours. In the second step, three samples presented positive results for bacterial leakage during the period of 14 days, which two were from the T10 group and one from the T20 group. After this period all the samples presented viability for the bacterial test. Within the limitations of this study, it was concluded that the torque value influenced the HE implants bacterial microleakage and that the standardization of the test methodology offered lower operator variables.